Gut microbiota in pregnant Malaysian women: a comparison between trimesters, body mass index and gestational diabetes status - Bahiyah Abdullah; Suzanna Daud; Mohd Shafiq Aazmi; Mohd Yusri Idorus; Mas Irfan Jaya Mahamooth (BMC, 2022)
Abstract Background The primary purpose of the study is to determine the variation of gut microbiota composition between first (T1) and third trimester (T3); gestational diabetes mellitus (GDM) and non-gestational diabetes mellitus (NGDM); and also within a different category of Body Mass Index (BMI) of selected pregnant Malaysian women. Methods A prospective observational study on selected 38 pregnant Malaysian women attending a tertiary medical centre was carried out. Those with preexisting diabetes, metabolic syndrome or any other endocrine disorders were excluded. GDM was determined using oral glucose tolerance test (OGTT) while BMI was stratified as underweight, normal, pre-obese and obese. Fecal samples were then collected during the first trimester (T1) and the third trimester (T3). The V3-V4 region of 16S rRNA gene amplicon libraries were sequenced and analyzed using QIIME (version 1.9.1) and METAGENassist. Results Twelve women (31.6%) were diagnosed as GDM. A trend of lower α-diversity indices in GDM, pre-obese and obese pregnant women were observed. Partial Least Squares Discriminant Analysis (PLS-DA) shows a clustering of gut microbiota according to GDM status and BMI, but not by trimester. Genera Acidaminococcus, Clostridium, Megasphaera and Allisonella were higher, and Barnesiella and Blautia were lower in GDM group (P < 0.005). Obese patients had gut microbiota that was enriched with bacteria of Negativicutes and Proteobacteria class such as Megamonas , Succinatimonas and Dialister (P < 0.005). The normal and mild underweight profiles on the other hand had a higher bacteria from the class of Clostridia (Papillibacter , Oscillibacter , Oscillospira , Blautia , Dorea) and Bacteroidia (Alistipes , Prevotella , Paraprevotella) (P < 0.005). Conclusion The prevalence and variation of several key bacteria from classes of Negativicutes, Clostridia and Proteobacteria has potential metabolic links with GDM and body weight during pregnancy which require further functional validation.